Optimalisasi pengetahuan gangguan menstruasi dan pramenstrual dysphoric disorder (PMDD) pada remaja putri - Ayu, Shinta Arini; Putri, Nazmi Rizkania S; Ibrahim, Nofah Maulani; Aliyah, Nurul Hamidatul; Aziz, Ujang Ahmad; Pauzi, Yogi; Utomo, Mohamad Iqbal Adityo Dwi (Holistik Jurnal Kesehatan, 2026)
Background: Menstruation and premenstrual disorders remain sensitive issues rarely discussed openly among adolescent girls in Indonesia. This is due to a lack of communication and education, resulting in a low level of understanding among adolescents regarding the menstrual process and its associated disorders. According to the Indonesian Demographic and Health Survey (IDHS), one in five adolescent girls had never discussed menstruation before menarche. This limited knowledge can increase the risk of menstrual disorders, including premenstrual dysphoric disorder. Purpose: To increase adolescent girls' knowledge regarding menstrual disorders and premenstrual dysphoric disorder through health education activities. Method: This study used a pre-experimental approach with a one-group pre-test and post-test design. This study was conducted at the Mulya Bakti Mandiri Cibeber Vocational High School Hall, Cianjur Regency in 2024. The sample involved in this study was 30 female students. The instrument used was a knowledge questionnaire about menstrual disorders and premenstrual dysphoric disorder. Health education was conducted through lectures, interactive discussions, educational video screenings, and leaflet distribution. Data were analyzed univariately. Results: Before the intervention, 82.5% of female students had a knowledge level of less than adequate. After the health education, knowledge increased significantly, with all students ranked as having a very good understanding of menstrual disorders and premenstrual dysphoric disorder. Conclusion: Health education has been proven effective in increasing adolescent girls' knowledge of menstrual disorders and premenstrual dysphoric disorder. Furthermore, structured health education using a variety of media can be a preventative measure to increase adolescent girls' understanding and preparedness in addressing reproductive health issues. Suggestion: Health providers can provide consistent education so that adolescent girls can recognize, take preventative measures, and develop positive behaviors to reduce the prevalence of premenstrual dysphoric disorder in adolescent girls.   Keywords: Adolescent Girls; Knowledge; Menstrual Disorders; Premenstrual Dysphoric Disorder.   Pendahuluan: Menstruasi dan gangguan pra menstruasi masih menjadi isu sensitif yang jarang dibicarakan secara terbuka di kalangan remaja putri di Indonesia. Hal ini karena kurangnya komunikasi dan edukasi, sehingga menyebabkan rendahnya pemahaman remaja terkait proses menstruasi dan gangguan yang menyertainya. Berdasarkan Survei Demografi dan Kesehatan Indonesia (SDKI), satu dari lima remaja putri tidak pernah berdiskusi mengenai menstruasi sebelum mengalami menarche. Pengetahuan yang minim ini, dapat meningkatkan risiko terjadinya gangguan menstruasi, termasuk gangguan premenstrual dysphoric disorder (PMDD). Tujuan: Untuk meningkatkan pengetahuan remaja putri terkait gangguan menstruasi dan premenstrual dysphoric disorder (PMDD) melalui kegiatan penyuluhan kesehatan. Metode: Penelitian ini menggunakan pendekatan pra-eksperimental desain one group pre-test and post-test. Penelitian ini dilaksanakan di Aula SMK Mulya Bakti Mandiri Cibeber, Kabupaten Cianjur pada tahun 2024. Sampel yang dilibatkan pada penelitian ini sebanyak 30 siswi. Instrumen yang digunakan berupa kuesioner pengetahuan tentang gangguan menstruasi dan pramenstrual dysphoric disorder (PMDD). Penyuluhan kesehatan yang dilakukan melalui metode ceramah, diskusi interaktif, pemutaran video edukasi, dan pembagian leaflet dan data dianalisis secara univariat.  Hasil: Sebelum intervensi, sebanyak 82.5% siswi memiliki tingkat pengetahuan dalam kategori kurang paham. Setelah diberikan penyuluhan kesehatan, terjadi peningkatan pengetahuan secara signifikan, seluruh siswa berada pada kategori sangat memahami terkait gangguan menstruasi dan premenstrual dysphoric disorder (PMDD). Simpulan: Berdasarkan penyuluhan kesehatan terbukti efektif dalam meningkatkan pengetahuan remaja putrid mengenai gangguan menstruasi dan premenstrual dysphoric disorder (PMDD). Selanjutnya, pendidikan kesehatan yang terstruktur dan menggunakan media yang bervariasi dapat menjadi upaya preventif dalam meningkatkan pemahaman dan kesiapan remaja putri dalam menghadapi masalah kesehatan reproduksi. Saran: Pihak kesehatan dapat memberikan penyuluhan secara konsisten agar remaja putri dapat mengenali, melakukan pencegahan, dan membentuk perilaku positif untuk menurunkan prevalensi PMDD pada remaja putri.   Kata Kunci: Gangguan Menstruasi; Pengetahuan; Pramenstrual Dysphoric Disorder (PMDD); Remaja Putri.